2015
DOI: 10.3813/aaa.918903
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acoustic Intensity, Spectrum, and Duration on Global Loudness Change

Abstract: Global loudness change is apost-stimulus retrospective judgement that measures listeners' overall impressions of loudness change in response to stimuli with continuous increases (up-ramps)a nd decreases (down-ramps) of acoustic intensity that are otherwise acoustically identical. Past results indicate that global loudness change is significantly greater in response to up-ramps relative to down-ramps for tonal stimuli (e.g., vowel)b ut not white-noise. An adaptive perceptual bias for up-ramp tonal stimuli has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Varying the range of intensity change within a ramped stimulus would intrinsically vary the rate of intensity change over a ramp's 1-s duration. The rate of intensity change per unit time is a key indicator of the perceived velocity of motion from a sound source (Carlile & Leung, 2016) and has been shown to influence perceptual asymmetries in both subjective duration and loudness change (Meunier et al, 2014;Olsen & Herff, 2015). Furthermore, the linear change of intensity used in the present study indicated a decelerating approaching object in the environment, rather than a constant-velocity approach (Neuhoff, 2001).…”
Section: Effects Of Acoustic Intensity On Sound Source Localizationmentioning
confidence: 59%
See 1 more Smart Citation
“…Varying the range of intensity change within a ramped stimulus would intrinsically vary the rate of intensity change over a ramp's 1-s duration. The rate of intensity change per unit time is a key indicator of the perceived velocity of motion from a sound source (Carlile & Leung, 2016) and has been shown to influence perceptual asymmetries in both subjective duration and loudness change (Meunier et al, 2014;Olsen & Herff, 2015). Furthermore, the linear change of intensity used in the present study indicated a decelerating approaching object in the environment, rather than a constant-velocity approach (Neuhoff, 2001).…”
Section: Effects Of Acoustic Intensity On Sound Source Localizationmentioning
confidence: 59%
“…Specifically, continuous increases (or up-ramps) of intensity are associated with looming sound sources in the environment, and continuous decreases (or down-ramps) of intensity are associated with receding sound sources (Neuhoff, 1998;Olsen, Stevens, & Tardieu, 2010). In psychoacoustic experiments, asymmetries in the perception of up-ramps and down-ramps have been reported in the context of subjective duration (DiGiovanni & Schlauch, 2007;Grassi & Darwin, 2006;Meunier, Vannier, Chatron, & Susini, 2014), global loudness (Ponsot, Meunier, Kacem, Chatron, & Susini, 2015;Stecker & Hafter, 2000), and loudness change (Neuhoff, 1998;Olsen & Herff, 2015;Teghtsoonian, Teghtsoonian, & Canévet, 2005). To summarize this literature, up-ramps are commonly perceived as being louder, longer, and covering a greater magnitude of loudness change than down-ramps (for a review, see Olsen, 2014).…”
mentioning
confidence: 99%
“…Theys howed no influence of frequencyo nt he effect, ad ecrease of the effect for broad-band noise compared to pure tones and also adecrease when the overall levelincreases. Olsen and Herff [4] also used rising and falling stimuli buti nc ontrast to the study by Ponsot and colleagues [3] theym easured the perceivedloudness change and howthis is influenced by spectrum, intensity and duration. Theys howed an end-levelr ecencye ff ect when global loudness change is measured.…”
mentioning
confidence: 94%
“…They found that loudness is the main factor used by participants to judge the similarity between sounds. Despite this importance of loudness in auditory perception of sounds, the temporal aspects described in [2,3,4,5] are still not included in current loudness models. This may be part of the reason whyd ynamic models are not always predicting loudness of time-varying sounds as shown in [7] and [8].…”
mentioning
confidence: 98%
See 1 more Smart Citation